A new species of Jurasai Rosa et al., 2020 and the first record of the family Jurasaidae (Coleoptera: Elateroidea) in the northern Brazilian Atlantic Forest - Nunes, João Paulo; Nascimento, Matheus; Pereira-Colavite, Alessandre (Zootaxa, 2023)
A new species, Jurasai parahybanum sp. nov., from the recently discovered elateroid family Jurasaidae is described. This is the first record of the family to Paraíba state and the Northern Atlantic Forest of Brazil. Photographs and drawings of the important morphological characters of the new species are provided. An updated key and distribution map to the known species of the family are provided.